Analysis Of The Aerospace & Defence Industry – Tata Consultancy Services - Maity, Amitkumar; Bhat, Sangeetha; Tangri, Joshna (2012)
This is a group management project which will fulfil the objective proposed by Tata Consultancy Services (TCS) - Strategic Analysis of Aerospace and Defence Industry.